PROSPECTS FOR THE DEVELOPMENT OF UKRAINE'S LIGHT INDUSTRY DURING MARTIAL LAW - PAKHOLIUK, Olena; ANDRIEVYCH, Tetiana; MELNYK, Dmytro; HLUSHENKO, Oleh (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article investigates the state and development prospects of Ukraine's light industry under the conditions of the Russian Federation's military aggression, which has been ongoing since February 2022. The study analyzes the impact of the war on production capacities, employment, foreign economic activity, and structural changes within the sector. It is established that approximately 70% of sewing factories continue to operate, and most enterprises have adapted to new conditions through reorientation to military orders and diversification of activities. At the same time, the industry faces critical challenges: labor shortages due to mobilization and employee relocation, electricity supply disruptions, rising raw material and production costs, unstable demand, and short-term orders.According to 2023 data, Ukraine had over 19,700 manufacturers of clothing, footwear, textiles, and leather goods, the majority of which are small and medium-sized enterprises. Despite the increase in the number of enterprises, the industry's turnover decreased by 13%, reflecting the significant impact of the war on economic indicators. Meanwhile, new promising segments have emerged, including military clothing, homewear, and wedding attire, providing potential for domestic market growth and export opportunities.The article highlights the sector’s foreign trade aspects: imports mainly come from China and Turkey, while exports are primarily directed to European countries, underscoring the need to develop domestic production and modernize enterprises for integration into global value chains. It is also noted that Ukrainian designers are gaining international recognition by combining traditional motifs with contemporary trends, contributing to cultural diplomacy and the promotion of national brands.The study further evaluates enterprise expectations regarding development prospects, uncertainty levels, and the financial and economic state of the industry. It is concluded that Ukraine’s light industry has significant potential for economic recovery, enhancing competitiveness, and integration into the EU market through production modernization, development of local supply chains, and the implementation of innovative management strategies.
Keywords: light industry; textile industry; war in Ukraine; foreign economic activity; production modernization; international markets